(untitled) (Global Journal of Computer Science and Technology, 2023)
A Mobile Adhoc networks also known as MANET or Wireless Adhoc Network is a network that usually has aroutable networking environment on top of a Link Layer ad hoc network It consist of a set of mobile nodes connected wirelessly in a self-configured self-healing network without having a fixed infrastructure Recent studies and fieldwork have pointed in the direction of making MANETS a publicly viable option in the event of another world event crisis such as the recent COVID-19 pandemic As opposed to their traditional military and emergency uses this has become a focal point due to the evident strain that was observed on mainstream Internet Service Providers as substantial adjustments had to be made to facilitate a new working-from-home public A primary aspect that must be considered before public adoption is addressing the issue of MANET risk and Security which leads into identifying and classifying risks associated with MANETS This paper seeks to analyze the various existing fields and meta-data within various networking datasets protocols as well as scenarios and subsequently establish what aspects of existing network traffic can be classified into axioms Risk Classifying arguments to determine Risk Profiles of MANETS The paper also seeks to determine and propose the ideal data fields within Network traffic for classifying Risk Profiles